The Ubiquitous Phenomena Of Dowry Practice And Its Relation With Women Prestige In District Swabi-Pakistan - Aman Ullah, Dr, Liqat Ali, Hina Ashraf, Dr. Hussain Ali, Sania Gul, Muhammad Tariq (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The main theme of the current study was to investigate the stimulants and negative impacts of high dowry practice with relation women's prestige in district Swabi. A total of 378 females were selected randomly through a proportional allocation method. The result of the study was analyzed into percentages and frequency while, to quantify the relationship between dowry practice and women prestige, the Chi-Square test was used. It has been inferences from the study findings that dowry is a scourge that is deeply embedded in our society and needs to be banned immediately before it could gulf us all. It is a herculean task to nip this evil in the bud. However gradual efforts should be taken to achieve this end. Dowry is also triggered intense conflicts within the society. It inculcates avarice and lust for materialism in the society. The study recommended that both government and other builders of the social fabric should work on it, in order to ban this evil practice. Moreover, to curb this malpractice it is highly recommended that we must bring social awareness in the society at the grass-root level.